The Role of the Surrounding Environment in Improving English Ability and Developing Students’ Vocabulary - Nabila Irsani; Nabila Laila; Nabila Dwi Hardiana; Natasya Aisyah; Natasya Herza Harahap; Siti Ismahani (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2023)
Language plays a vital role in everyday life, communicating ideas to others. Language skills are basic subjects for everyone to draw away from the feelings, desires, opinions, and needs of each person and each individual. Student English skills should be enhanced when English is already an international language. The neighborhood also played an important role in improving English quality. This study aims to know the role of the environment in the increasing abilities of students' English. Next to know the role of the environment in adding a student's English vocabulary. The study used in this study is a qualitative method using interview methods with MA Darurrachmad students. Studies suggest that the environment and schools of students greatly influence the promotion of improved English ability and the development of learners' vocabulary.